Anti-microbial, Anti-oxidant, Anti-diabetic study of leaf Essen-tial Oil of Eryngium foetidum L. Along with the Chemical Profiling Collected from North East India. Issue 6 (2nd November 2022) - Paw, Manabi; Gogoi, Roktim; Sarma, Neelav; Saikia, Samarjeet; Chanda, Sanjoy Kumar; Lekhak, Himangshu; Lal, Mohan
Abstract: Eryngium foetidum L., is locally known as Mexican coriander which is medicinally important and belongs to the family Apiaceae. Industrially and pharmacologically important chemical compounds were reported in the leaf essential oil of this species. In this study leaf essential oil extraction was done by the use of hydro distillation and pharmacological potentials like anti-microbial, anti-oxidants, anti-diabetic studies were also performed as per standard methods. The compound identification was carried out by Gas chromatography/mass spectroscopy (GC/MS). A total of 98.76% percentages of compounds were identified that includes 2-dodecenal (87.85%) as the main compound followed by 2, 4, 6-trimethyl benzaldehyde (4.06%), ( E )-tetradec-2-enal (1.66%), diepicedrene-1-oxide (1.62%), dodecanal (1.19%), decanal (0.38%), 1-dodecanal (0.51%), dodecanoic acid (0.6%), 2, 4, 6-trimethyl- phenol (0.42%) were found as the minor constituent in E. foetidum leaf essential oil. The essential oil exhibited IC50 45.13 µL/mL of DPPH radical scavenging potential while IC50 13.96 µL/mL was in ABTS assay. The anti-diabetic potential of leaf essential oil was also performed using α-amylase inhibitory methodology. Additionally, antidiabetic activity was exhibited by the essential oil with IC50 153.98 µL/mL. Antimicrobial potential was also checked using both four strains of bacteria and fungi respectively and found that it had a comparable potential to the standard drugs.